2020
DOI: 10.17509/ijal.v10i1.25063
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian students’ perceived benefits of the micro-teaching course to their teaching internship

Abstract: This study aims to explore student-teachers’ perceptions of the benefits of micro-teaching class they have attended to their teaching internship. It also seeks to identify the most and the least likely aspects of teaching which have been sufficiently covered in the micro-teaching course. The participants of this study were ten senior EFL students at a State Islamic University in Indonesia who have taken a micro-teaching class and teaching internship program. The data from interviews and students’ written narra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
1
7
0
1
Order By: Relevance
“…Internship is considered as a bridge to the real world of work as students have the chance to apply theoretical and practical knowledge obtained in a classroom to the actual work setting [43]- [46]. This paper's findings also corroborate in the previous studies that internship program also enhances the PTs' pedagogical competence and professional beliefs [47], [48]. The individual schema of prospective teachers is a product of their numerous encounters with their students, teachers, parents, and school administrators.…”
Section: Teaching Internship As An Ultimate Path Towards Becoming a Teachersupporting
confidence: 81%
“…Internship is considered as a bridge to the real world of work as students have the chance to apply theoretical and practical knowledge obtained in a classroom to the actual work setting [43]- [46]. This paper's findings also corroborate in the previous studies that internship program also enhances the PTs' pedagogical competence and professional beliefs [47], [48]. The individual schema of prospective teachers is a product of their numerous encounters with their students, teachers, parents, and school administrators.…”
Section: Teaching Internship As An Ultimate Path Towards Becoming a Teachersupporting
confidence: 81%
“…(Manasikana & Hartono, 2021). It has been found that the internship affords student-teachers the chance to gain insights from authentic teaching experiences, contributing to their overall development (Zulfikar et al, 2020). This aligns with the idea that internships are central to teacher preparation and can significantly impact the reflective ability and instructional skills of teacher candidates (Nagro et al, 2017).…”
Section: Internship Programs and Language Scaffoldingmentioning
confidence: 81%
“…Sebagai hasil dari praktik Micro Teaching yang telah dilaksanakan, mayoritas peserta tidak mampu mengelaborasi bahasa mereka sendiri ketika berpartisipasi dalam praktek ini.. Hal ini karena mayoritas peserta lebih sering menggunakan bahasa Indonesia dalam bahasa sehari -hari, bukan bahasa Inggris. Sehingga Micro Teaching dapat digunakan sebagai salah satu metode untuk mengajari mereka cara menulis dan berbicara dalam bahasa Inggris (Zulfikar et al, 2020). Pentingnya belajar bahasa Inggris di masa sekarang ini tidak bisa tidak dapat diremehkan atau diabaikan melihat bahasa Inggris sebagai bahasa yang digunakan di sebagian besar dunia.…”
Section: Pendahuluanunclassified